1990
DOI: 10.1152/ajpendo.1990.259.4.e477
|View full text |Cite
|
Sign up to set email alerts
|

Effect of starvation on human muscle protein metabolism and its response to insulin

Abstract: Although starvation is known to impair insulin-stimulated glucose disposal, whether it also induces resistance to insulin's antiproteolytic action on muscle is unknown. To assess the effect of fasting on muscle protein turnover in the basal state and in response to insulin, we measured forearm amino acid kinetics, using [3H]phenylalanine (Phe) and [14C]leucine (Leu) infused systemically, in eight healthy subjects after 12 (postabsorptive) and 60 h of fasting. After a 150-min basal period, forearm local insulin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
45
0
1

Year Published

1992
1992
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 9 publications
4
45
0
1
Order By: Relevance
“…Although nitrogen balance is negative in both cases (Svanfeldt et al, 2006), protein breakdown in starvation alone remains at near-normal values, whereas protein synthesis decreases (James, 1981;Arnal et al, 1987;Waterlow, 1995;Volpi et al, 1998) or, according to other reports, protein breakdown increases and protein synthesis remains unchanged (Frexes-Steed et al, 1990;Fryburg et al, 1990;Waterlow, 1995). A possible explanation for the differing response to fasting that occurs in injured vs healthy individuals is the different metabolic needs of the two situations.…”
Section: Discussionmentioning
confidence: 98%
“…Although nitrogen balance is negative in both cases (Svanfeldt et al, 2006), protein breakdown in starvation alone remains at near-normal values, whereas protein synthesis decreases (James, 1981;Arnal et al, 1987;Waterlow, 1995;Volpi et al, 1998) or, according to other reports, protein breakdown increases and protein synthesis remains unchanged (Frexes-Steed et al, 1990;Fryburg et al, 1990;Waterlow, 1995). A possible explanation for the differing response to fasting that occurs in injured vs healthy individuals is the different metabolic needs of the two situations.…”
Section: Discussionmentioning
confidence: 98%
“…18 As in our study, a sustained insulin secretion with CR has also been found by other studies to prevent unfavorable protein catabolism. 43 Effect of 1-week OF Fasting and postprandial IS were significantly impaired after 1-week OF ( þ 60% energy). Concomitantly, postprandial insulin secretion increased.…”
Section: Discussionmentioning
confidence: 99%
“…Leucine and phenylalanine specific activity were determined as previously described (18,19). Data analysis.…”
Section: Methodsmentioning
confidence: 99%